MODUS DALAM NOVEL PRIDE AND PREJUDICE KARYA JANE AUSTEN - PITOY, SRI FITRI WILAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT                        This research is entitled ?Mood in novel Pride and Prejudice by Jane Austen?? as the requirement to accomplish the Bachelor Degree in English Linguistic at Faculty of Hunanities, Sam Ratulangi University. This research aims to identify, classify, and analyze the types and the function of mood which found in Novel Pride and Prejudice by Jane Austen.                       The writer used theory from Aarts and Aarts (1982) which divided the mood into three parts, they are: Indicative mood, Subjunctive mood and Imperative mood. Frank (1972) divided the theory of function into three parts, they are; Imperative mood functional to declare command, request, and instruction; Subjunctive mood functional to declare uncertainty, wish, and encourage; Indicative mood functional to declare all situation without the imperative and subjunctive mood. Moreover, the method used in this research is descriptive method. The data of mood is taken from the sentences in novel Pride and Prejudice.            The result of this research shows 41 function. The kinds of mood which found are 41 data, they are 12 imperative moods to express commands or request. 9 subjunctive moods to signal unreality, wishes, conjecture or urgency and 21 indicative moods.------------------------------------Keywords: syntax, mood, novel